2018
DOI: 10.1136/jmedgenet-2018-105672
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of parental mosaicism in SCN1A-related epilepsy by single-molecule molecular inversion probes and next-generation sequencing

Abstract: BackgroundDravet syndrome is a severe genetic encephalopathy, caused by pathogenic variants in SCN1A. Low-grade parental mosaicism occurs in a substantial proportion of families (7%–13%) and has important implications for recurrence risks. However, parental mosaicism can remain undetected by methods regularly used in diagnostics. In this study, we use single-molecule molecular inversion probes (smMIP), a technique with high sensitivity for detecting low-grade mosaic variants and high cost-effectiveness, to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
(17 reference statements)
2
11
1
Order By: Relevance
“…As Sanger sequencing is known to have a detection limit of 10% to 20% [13], low-grade somatic mosaicisms might only be detectable by more sensitive methods. It could be more frequent than previously assumed as deep sequencing of parental samples from children with de novo variants in genes causative of epileptic encephalopathy revealed low levels of somatic mosaicism ranging from 1-10% in blood in 5-6% of cases [14,15]. However, as deep sequencing was negative in our patient s father, we rather suggest a germline mutation as the underlying cause.…”
Section: Significance and Transmission Of The Polg Variantscontrasting
confidence: 50%
“…As Sanger sequencing is known to have a detection limit of 10% to 20% [13], low-grade somatic mosaicisms might only be detectable by more sensitive methods. It could be more frequent than previously assumed as deep sequencing of parental samples from children with de novo variants in genes causative of epileptic encephalopathy revealed low levels of somatic mosaicism ranging from 1-10% in blood in 5-6% of cases [14,15]. However, as deep sequencing was negative in our patient s father, we rather suggest a germline mutation as the underlying cause.…”
Section: Significance and Transmission Of The Polg Variantscontrasting
confidence: 50%
“…Recent studies have shown that germline and somatic mosaicism is present in genes related with severe encephalopathies such as Dravet syndrome [24,25], focal cortical dysplasia [26] and intellectual disability [27]. Mosaicism is being postulated as the cause to explain differential phenotype expression of the disease among patients (somatic mosaicism due to a postzygotic mutation) and to explain recurrent mutations in the same family assumed de novo (due to low-grade parental mosaicism).…”
Section: New Technologies For a Rare Genetic Diagnosismentioning
confidence: 99%
“…Previous cohort studies of de novo variants have reported varying prevalence of parental mosaicism (Table 3) (Breuss et al, 2020;Campbell, Yuan, et al, 2014;de Lange et al, 2019;Hu et al, 2019;Jónsson et al, 2018;Legrand et al, 2019;Møller et al, 2019;Myers et al, 2018;Nakayama et al, 2018;Xu et al, 2015;Yang et al, 2017Yang et al, , 2019. In contrast to parental mosaicism studies on peripheral blood, sperm has only been investigated in three cohorts previously (Breuss et al, 2020;Yang et al, 2017Yang et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Parental investigations most often depend on genetic analysis of blood‐derived DNA. Currently, a recurrence risk of 1% is commonly used during counselling (Campbell, Stewart, et al, 2014; de Lange et al, 2019; Myers et al, 2018; Röthlisberger & Kotzot, 2007). However, the recurrence risk may be higher or lower depending on if one of the parents is a germline mosaic or not.…”
Section: Introductionmentioning
confidence: 99%